Meta Analysis of the Relationship between Tea Drinking Habits and the Incidence of Anemia in Pregnant Women - Samara Rahma Dania; Yulia Lanti Retno Dewi; Eti Poncorini Pamungkasari (Masters Program in Public Health, 2022)
Background: Anemia is a nutritional problem that needs attention and is one of the public health problems in Indonesia. One of the causes of anemia in pregnant women is the consumption of tea, where tea contains polyphenols which can inhibit the absorption of iron. The purpose of this study was to analyze the available evidence related to the relationship between tea drinking habits and the incidence of anemia in pregnant women.Subjects and Method: This study uses a systematic review and meta-analysis with PICO, namely, population= pregnant women. Intervention= drinking tea. Comparison= don't drink tea. Outcome = incidence of anemia. Article searches were conducted using electronic databases such as Google Scholar and PubMed between 2013 and 2022. The keywords used were: [(